Human Resource Management in Pesantren-Based Islamic Secondary Education - Muttaqin, Moch Zaimul; Rofiki, Moh (Kartika: Jurnal Studi Keislaman, 2025)
This article examines human resource management (HRM) strategies for improving teacher productivity at Madrasah Tsanawiyah Nurul Jadid, which operates within a pesantren environment. The study focuses on humanistic, participatory, and contextual HRM practices that align with the characteristics of Islamic education. A qualitative approach with a case study design was employed to explore in depth the experiences and perspectives of the principal, the vice principal for curriculum, and teachers regarding professional development and performance management. Data were collected through in-depth interviews and documentation, then analyzed thematically. The findings indicate that teacher productivity is enhanced through several key strategies, including a humanistic approach to supervision and coaching, peer-based performance assessment, educationally oriented attendance evaluation, needs-based teacher training, and the provision of awards for exemplary teachers. These strategies function not only as mechanisms of work control but also as means of strengthening professional responsibility, motivation, and a collaborative culture among teachers. The study highlights the distinctive nature of HRM in pesantren-based madrasahs, emphasizing a balance between professionalism and Islamic values